دور حاضنات الأعمال في دعم الروح الريادية لدى الطلبة دراسة ميدانية لطلبة سنة ثانية ماستر كلية العلوم الاقتصادية والتجارية وعلوم التسيير بجامعة باتنة 1 - خزار, مريم; غربي, العيد (جامعة الوادي - University of Eloued, 2023)
This study aims to highlight the role of business incubators in supporting the entrepreneurial spirit of university undergraduates students, as they are considered one of the most important mechanisms that contribute to providing entrepreneurial projects with all the support and assistance factors needed. In this paper, the analytical descriptive method has been adopted in order to understand the theoretical aspect of the study subject and highlight the various concepts related to the variables of the study. The researcher also built a survey based on some previous studies. The study population was represented by Second-year Master's students at the Faculty of Economics at the University of Batna1. Where 130 questionnaires were distributed and a hundred of which were retrieved and considered valid for statistical analysis. SPSS program was used and the study revealed the following set of results: -There is an entrepreneurial desire among the students, but this desire lacks some entrepreneurial characteristics necessary to ensure the good conduct of ideas and projects. -There is a relatively weak relationship between the business incubator's activity and the entrepreneurial spirit of the students
The Role of Business Incubators in Supporting The Entrepreneurial Spirit of University Undergraduates Students Empirical Study For Second Year Master Students Faculty of Economic Commercial And Management Sciences University Batna 01
مقال
Keywords: حاضنات الأعمال ; روح ريادية ; ريادة الأعمال ; طلبة: keywords1; Business Incubators, Entrepreneurial Spirit, Entrepreneurship, students